Accruing Competitive Advantage from REIT: An Assessment of The Indian Real Estate Industry - Gupta, Mohit (2007)
The real estate sector in India has assumed a growing importance with the liberalization of the economy. The consequent increase in business opportunities and migration of the labor force has, in turn increased the demand for commercial and housing space. However, lack of funds, poor transparency level, complex and hazy regulations and policies, and lack of financial infrastructure impede the growth of the Indian real estate industry. Moreover, it seems that Indian real estate companies were exposed to the risk of recession, as real estate market exhibits cyclic behavior. Therefore, real estate companies have to form rational strategies to sustain during the recession period. Given the changes in the business environment, restructuring business models seems more appropriate as a strategy for the Indian real estate companies. In this sense, Real Estate Investment Trust (REIT) seems a promising model for managing the real estate business in India. However, there is yet no REIT legislation in India, nevertheless, it is in the final stage of planning and soon would be launched in Indian market. This work seeks to address this gap by analyzing whether REIT would be successful in India and identifying the motivating factors for the real estate companies to adopt this model, and recognizing the key issues influencing the successful implementation of REIT. Using the data collected from the interviews of real estate managers, findings were quite encouraging and REIT seems a prospective business model. Moreover, six direct and three indirect motivating factors were identified. Knowledge of the property management team, reputation of the sponsor, relationship and network, and governance were the major sources of competitive advantage and facilitate the successful implementation of the REIT. Conclusion and implications are drawn and discussed to close the work.